IN ANTICIPATION OF TECTONIC CHANGES IN WORLDVIEW - Zafar Elferuz (Bright Mind Publishing, 2025)
The purpose of this study is to determine whether there are signs of logical similarity and harmony between the laws of nature and the social world, society. Such similarities certainly exist; however, since ancient times they have largely remained outside the field of human attention and have been reflected mainly in folk proverbs and sayings. The importance of fundamental discoveries and inventions in expanding social consciousness and elevating societal development to a higher level is undeniable. Moreover, they play an enormous role in deepening the thinking of an individual person; unfortunately, new discoveries and inventions are rarely subjected to philosophical analysis. As a result, discoveries do not go beyond the boundaries of a narrow scientific domain and therefore fail to reach public consciousness. The time has come to raise the level of understanding and interpretation of natural phenomena and laws and, consequently, to elevate our worldview to a higher stage.
Keywords: Fundamental sciences, social sciences, Prigogine’s dynamic chaos, Stepin’s levels, Mandelbrot’s self-similarity, unification.